Problem-based learning approach to mathematics at the polytechnic level : an exploratory study - Chee, Jonathan Wing Hong. (2008)
This exploratory study investigates the views of polytechnic students on problem-based learning as an alternative approach to the traditional mode of learning Mathematics.